PENDEKATAN TERPADU DALAM PERSIAPAN UTBK - Elisya, Nur; Jupri, Al; Wahab A, Abdul; Izzah, Aqidatul; Laia, Harun Onesimus; Candraningsih, Yosy; Sungkono, Sugeng; Marjud, Fujiama (Universitas Pattimura, 2025)
Preparing for the Computer-Based Written Examination (UTBK) poses a significant challenge for high school students, not only in terms of academic mastery but also in mental readiness to face exam pressure. One of the main issues identified is math anxiety, which can disrupt concentration and lower academic performance. To address this challenge, the SMART UTBK program was developed as a comprehensive approach that integrates anxiety management strategies with competency strengthening through UTBK-style practice questions. The program includes educational webinars that discuss techniques to overcome math anxiety and offer practical tips for solving UTBK math problems, as well as online tryout sessions designed to simulate real test conditions. A total of 100 senior high school students participated in this initiative. Evaluation results indicated that over 70% of participants found the math anxiety material helpful in managing excessive exam-related stress and reported improved understanding of problem-solving strategies. The tryout sessions were also considered representative and effective in helping students assess their readiness in a realistic context. This program not only addresses technical knowledge needs but also provides the psychological support essential for students facing university entrance exams. The SMART UTBK program underscores the importance of integrative interventions, demonstrating that equipping students both psychologically and academically can significantly enhance their emotional and cognitive preparedness